Pregnancy intention data completeness, quality and utility in population-based surveys: EN-INDEPTH study - Judith Yargawa; Kazuyo Machiyama; Victoria Ponce Hardy; Yeetey Enuameh; Edward Galiwango; Kassahun Gelaye; Kaiser Mahmud; Sanne M. Thysen; Damazo T. Kadengye; Vladimir Sergeevich Gordeev; Hannah Blencowe; Joy E. Lawn; et al. (BMC, 2021)
Abstract Background An estimated 40% of pregnancies globally are unintended. Measurement of pregnancy intention in low- and middle-income countries relies heavily on surveys, notably Demographic and Health Surveys (DHS), yet few studies have evaluated survey questions. We examined questions for measuring pregnancy intention, which are already in the DHS, and additional questions and investigated associations with maternity care utilisation and adverse pregnancy outcomes. Methods The EN-INDEPTH study surveyed 69,176 women of reproductive age in five Health and Demographic Surveillance System sites in Ghana, Guinea-Bissau, Ethiopia, Uganda and Bangladesh (2017-2018). We investigated responses to survey questions regarding pregnancy intention in two ways: (i) pregnancy-specific intention and (ii) desired-versus-actual family size. We assessed data completeness for each and level of agreement between the two questions, and with future fertility desire. We analysed associations between pregnancy intention and number and timing of antenatal care visits, place of delivery, and stillbirth, neonatal death and low birthweight. Results Missing data were <2% in all questions. Responses to pregnancy-specific questions were more consistent with future fertility desire than desired-versus-actual family size responses. Using the pregnancy-specific questions, 7.4% of women who reported their last pregnancy as unwanted reported wanting more children in the future, compared with 45.1% of women in the corresponding desired family size category. Women reporting unintended pregnancies were less likely to attend 4+ antenatal care visits (aOR 0.73, 95% CI 0.64-0.83), have their first visit during the first trimester (aOR 0.71, 95% CI 0.63-0.79), and report stillbirths (aOR 0.57, 95% CI 0.44-0.73) or neonatal deaths (aOR 0.79, 95% CI 0.64-0.96), compared with women reporting intended pregnancies. We found no associations for desired-versus-actual family size intention. Conclusions We found the pregnancy-specific intention questions to be a much more reliable assessment of pregnancy intention than the desired-versus-actual family size questions, despite a reluctance to report pregnancies as unwanted rather than mistimed. The additional questions were useful and may complement current DHS questions, although these are not the only possibilities. As women with unintended pregnancies were more likely to miss timely and frequent antenatal care, implementation research is required to improve coverage and quality of care for those women.